REDESAIN KEMASAN MADU TRIGONA DAN KREASI KORAN BEKAS UNTUK RESTORASI EKONOMI UMKM BALI - Darmawan, Andreas James (Telkom University, 2023)
An effort and enthusiasm for the Balinese economy to revive after the pandemic, where the Ministry of Tourism and Creative Economy provided packaging design assistance for Micro, Small and Medium Enterprises (MSMEs) in Tenganan Village and Carangsari Village, Bali. The urgency of this research is to respond to the problem raised by the Visual Communication Design Study Program Association (Asprodi) which is improving packaging design in the 8th batch of Packaging Design Surgery (BEDAKAN) program. This research focuses on two MSME products; packaging design for Trigona Honey